Alexander Humbold's Scientific Heritage in Geography Field - Mirzoyeva Istat Elmurodovna; Sobirova Dilorom Bobirjon kizi (Zien Journals, 2022)
The article deals with detailed information about the life and work of Alexander Humboldt, as well as his geographical views.
Keywords: Andes; Priney Peninsula; Emme Bonplan; Barometer-aneroid